Development of biological meniscus scaffold: Decellularization method and recellularization with meniscal cell population derived from mesenchymal stem cells. (April 2021) - Kara, Aylin; Koçtürk, Semra; Bilici, Gokcen; Havitcioglu, Hasan
Tissue engineering approaches which include a combination of cells and scaffold materials provide an alternative treatment for meniscus regeneration. Decellularization and recellularization techniques are potential treatment options for transplantation. Maintenance of the ultrastructure composition of the extracellular matrix and repopulation with cells are important factors in constructing a biological scaffold and eliminating immunological reactions. The aim of the study is to develop a method to obtain biological functional meniscus scaffolds for meniscus regeneration. For this purpose, meniscus tissue was decellularized by our modified method, a combination of physical, chemical, and enzymatic methods and then recellularized with a meniscal cell population composed of fibroblasts, chondrocytes and fibrochondrocytes that obtained from mesenchymal stem cells. Decellularized and recellularized meniscus scaffolds were analysed biochemically, biomechanically and histologically. Our results revealed that cellular components of the meniscus were successfully removed by preserving collagen and GAG structures without any significant loss in biomechanical properties. Recellularization results showed that the meniscal cells were localized in the empty lacuna on the decellularized meniscus, and also well distributed and proliferated consistently during the cell culture period (p < 0.05). Furthermore, a high amount of DNA, collagen, and GAG contents (p < 0.05) were obtained with the meniscal cell population in recellularized meniscus tissue. The study demonstrates that our decellularization and recellularization methods were effective to develop a biological functional meniscus scaffold and can mimic the meniscus tissue with structural and biochemical features. We predict that the obtained biological meniscus scaffolds may provide avoidance of adverse immune reactions and an appropriate microenvironment for allogeneic or xenogeneic recipients in the transplantation process. Therefore, as a promising candidate, the obtained biological meniscus scaffolds might be verified with a transplantation experiment.